2019
DOI: 10.1148/radiol.2019190613
|View full text |Cite
|
Sign up to set email alerts
|

A Roadmap for Foundational Research on Artificial Intelligence in Medical Imaging: From the 2018 NIH/RSNA/ACR/The Academy Workshop

Abstract: Imaging research laboratories are rapidly creating machine learning systems that achieve expert human performance using opensource methods and tools. These artificial intelligence systems are being developed to improve medical image reconstruction, noise reduction, quality assurance, triage, segmentation, computer-aided detection, computer-aided classification, and radiogenomics. In August 2018, a meeting was held in Bethesda, Maryland, at the National Institutes of Health to discuss the current state of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
175
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(186 citation statements)
references
References 84 publications
0
175
0
1
Order By: Relevance
“…Further, validation ideally occurs very frequently, interspersed between algorithm updates, and throughout the process of algorithm development. However, for a segmentation algorithm to be clinically applicable its outcome should be optimal, i.e., similar to the ground-truth, and therefore it's expected to require "some" user input (Langlotz et al, 2019). Our research aims to provide an approach to automate many aspects of user interaction and thus expedite large-scale validation.…”
Section: Discussionmentioning
confidence: 99%
“…Further, validation ideally occurs very frequently, interspersed between algorithm updates, and throughout the process of algorithm development. However, for a segmentation algorithm to be clinically applicable its outcome should be optimal, i.e., similar to the ground-truth, and therefore it's expected to require "some" user input (Langlotz et al, 2019). Our research aims to provide an approach to automate many aspects of user interaction and thus expedite large-scale validation.…”
Section: Discussionmentioning
confidence: 99%
“…Explainable Artificial Intelligence (XAI) is a relatively new set of techniques that combines sophisticated AI and ML algorithms with effective explanatory techniques to develop explainable solutions that have proven useful in many domain areas (Core et al, 2006;Samek et al, 2017;Yang and Shafto, 2017;Adadi and Berrada, 2018;Choo and Liu, 2018;Dosilovic et al, 2018;Holzinger et al, 2018;Fernandez et al, 2019;Miller, 2019). Recent work has suggested that XAI may be a promising avenue to guide basic neural circuit manipulations and clinical interventions (Holzinger et al, 2017b;Vu et al, 2018;Langlotz et al, 2019). We will develop this idea further here.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying and prioritizing diagnostic categorization is a major challenge in psychiatry which if not carried out correctly translates into inaccuracies in diagnostic labeling of biological data, such as medical imaging. Addressing these inaccuracies (which we refer to as label noise in a diagnostic classification problem setup) is an important topic of great interest that serves the ultimate goal of helping patients [9]. The application of artificial intelligence (AI) can be leveraged to help with this task and to achieve better results.…”
Section: Introductionmentioning
confidence: 99%